2010
DOI: 10.1590/s0103-90162010000200012
|View full text |Cite
|
Sign up to set email alerts
|

Humic substances isolated from residues of sugar cane industry as root growth promoter

Abstract: Plant growth promoting substances are widely used in modern agriculture. Several products in the market are humic substances isolated from different sources. The filter cake, a residue of sugar production, is a rich and renewable source of organic matter and these characteristics place the filter cake as a possible source of plant growth promoting substances. Humic acids (HA) from filter cake were characterized, and their effects as root growth promoters were evaluated. Chemical features of the HA were evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 42 publications
0
10
0
2
Order By: Relevance
“…Generally, the authors observed that the humic acids were uniform in composition as the compounds matured. Busato et al (2010) examined for humic substances extracted from sugarcane residue (from the pie filter industry) by FTIR and observed typical organic acid profiles with weak polyprotic acids in the presence of carboxylic groups, secondary amides, esters and phenolic groups. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, the authors observed that the humic acids were uniform in composition as the compounds matured. Busato et al (2010) examined for humic substances extracted from sugarcane residue (from the pie filter industry) by FTIR and observed typical organic acid profiles with weak polyprotic acids in the presence of carboxylic groups, secondary amides, esters and phenolic groups. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, filter cake (FC), a residue from the sugar industry, has great potential as soil amendment due to its high nutrient content (Busato et al, 2010). The use of FC as fertilizer is a traditional practice in many regions, although it can promote immobilization of soil nitrogen when incorporated directly into the soil, due to the stimulation of native microbial activity (Blagodatskaya & Kuzyakov, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Particularmente, são bem relatados os efeitos sobre o crescimento radicular (Canellas et al, 2002;Zandonadi et al, 2010;Busato et al, 2010;Aguiar et al, 2013 (Taiz & Zeiger, 2013). A bomba de prótons é o transporte ativo H + do citosol para parede celular e tonoplastos, podendo ocorrer redução de até duas unidades de pH comparado ao citosol (Taiz & Zeiger, 2013 (Taiz & Zeiger, 2013).…”
Section: Efeitos Da Aplicação De Soluções Contendo Substâncias Húmicaunclassified
“…Ca 2+ nas raízes das plantas tratadas com AH (Figura 19), isso veio acompanhado com um incremento de massa fresca das raízes de milho. Como a presença de AH, os processos de divisão e crescimento das raízes de milho são intensificados (Canellas et al, 2002;Busato et al, 2010;Zandonadi et al, 2010;Aguiar et al, 2013). (Haehnel, 1984 (Ferreira et al, 2001;Faquin, 2005;Taiz & Zeiger, 2013).…”
unclassified